Desempenho de redes cooperativas full-duplex baseadas em NOMA e seleção parcial de relays - Tregancini Junior, Anderson [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
With the rapidly increasing demand for wireless-based applications and services, the need to efficiently exploit the radio spectrum is imperative. In addition, fifth-generation (5G) networks must satisfy some requirements regarding the quality of service provided to their users, such as increased spectral efficiency, higher data rates and support for a massive number of connected devices. In light of this, non-orthogonal multiple acess (NOMA) and full-duplex relaying are technologies being considered, in order to achieve these objectives, as candidates to be part of the specifications of 5G networks. NOMA is a strategy whereby multiple users can share the same time, frequency or code resources, by adjusting their power allocation ratio, whereas full-duplex relaying allows to recover the spectral efficiency loss inherent to half-duplex relaying. Thus, the joint use of NOMA and full-duplex relaying has been drawing attention, due to the gains in spectral efficiency and data rate, as well as to the decrease in latency, in addition to taking advantage from the spatial diversity obtained through cooperative communications. This work analyzes the performance in terms of the outage probability for a NOMA-based cooperative scheme, which employs full-duplex relaying and the amplify-and-forward protocol, with partial relay selection. The considered system model consists of one source, two users, acessing the channel through NOMA, and a cluster of full-duplex relays. As contributions of this work, an exact expression in integral form, a lower-bound expression, an asymptotic expression at the high signal-to-noise ratio regime and an approximated losed-form expression are obtained. From the analytical expressions, the impact of the numbers of relays, the power allocation factor between users, and the residual self-interference inherent to full-duplex relaying is assessed on the performance of the proposed system. In addition, a performance comparison is...

Com o aumento acelerado da demanda por aplicações e serviços baseados em redes sem fio, a necessidade de explorar eficientemente o espectro radioelétrico é cada vez mais imperiosa. Além disso, existem requerimentos que as redes de quinta geração (5G) devem satisfazer em relação à qualidade de serviço fornecida a seus usuários, tais como aumento da eficiência espectral, fornecimento de taxas de dados cada vez mais elevadas e suporte a um número massivo de dispositivos conectados. Em vista disto, o acesso múltiplo não ortogonal (NOMA) e a retransmissão full duplex são tecnologias que vem sendo consideradas, a fim de alcançar estes objetivos, como candidatas a fazer parte das especificações das redes 5G. NOMA é uma estratégia em que múltiplos usuários podem compartilhar os mesmos recursos de tempo, frequência ou código, ajustando sua relação de alocação de potência, enquanto o modo de retransmissão full duplex permite recuperar a perda de eficiência espectral inerente ao modo de retransmissão half duplex. Desta forma, o uso combinado de NOMA com o modo de retransmissão full-duplex vem ganhando atenção, devido aos ganhos em eficiência espectral, taxa de dados e à diminuição da latência de transmissão, além de usufruir das vantagens em relação à diversidade espacial obtida através de comunicações cooperativas. Este trabalho analisa o desempenho em termos da probabilidade de outage para um esquema cooperativo baseado em NOMA, que emprega retransmissão full-duplex e o protocolo de retransmissão amplifica-e-encaminha com seleção parcial de relays. O modelo do sistema considerado consiste de uma fonte, dois usuários, os quais acessam o canal usando NOMA, e um cluster de relays full duplex. Como contribuições deste trabalho, são obtidas uma expressão exata em forma integral, uma expressão limitante inferior, uma expressão assintótica para o regime de alta relação sinal-ruído e uma...
Performance of full-duplex cooperative networks based on NOMA and partial relay selection
Keywords: Comunicações digitais; Sistemas de comunicação sem fio; Telecomunicações; Digital communications; Telecommunication; Wireless communication systems